Molecular epidemiology of macrolide resistant Group A streptococci from Puducherry, India: Macrolide resistant group A streptococci - Abraham, Tintu; Sistla, Sujatha (The Journal of Infection in Developing Countries, 2017)
Introduction: In penicillin allergic patients, macrolides are the most commonly used antibiotics for treating streptococcal infections, irrespective of the higher resistance rates. The objective of this study was to evaluate the comparative prevalence, phenotypes, and genetic determinants of macrolide resistance and associated emm types among different clinical isolates of Streptococcus pyogenes. Methodology: A total of 173 Streptococcus pyogenes isolates were examined for macrolide resistance phenotype by double-disc test, resistance determinants by multiplex PCR and emm genotyping. Results: Erythromycin resistance was found in 51.4% of isolates, with MIC90 ≥ 256 µg/mL Inducible phenotype was commonly found (iMLS, 67.4%) followed by the M phenotype (32.5%). Among these isolates, 65.1% harboured ermB and 32.5% mefA as sole macrolide resistance gene, whereas presence of both, ermB plus mefA was observed in 2.2% cases. The most common types among resistant strains were emm63 (11.2%), emm44 (6.7%), emm42 (5.6%), and emm75.3, emm82, emm85, emm92, emm111.1 (4.4% each). Statistically significant association was observed between emm63, emm44 and erythromycin resistance (p ≤ 0.05). Association of these emm types and macrolide resistance have not been reported earlier. Conclusion: Higher macrolide resistance in this study can be attributed to overuse and misuse of this antibiotic. These findings indicate that macrolides should not be empirically used for treating severe streptococcal infections.